Region-specific sympatho-adrenergic regulation of specialized vasculature in bone homeostasis and regeneration - Xu, Hao-Kun; Liu, Jie-Xi; Zheng, Chen-Xi; Liu, Lu; Ma, Chao; Tian, Jiong-Yi; Yuan, Yuan; Cao, Yuan; Xing, Shu-Juan; Liu, Si-Ying; Li, Qiang; Zhao, Ya-Juan; et al. (iScience, 2023)
Type H vessels couple angiogenesis with osteogenesis, while sympathetic cues regulate vascular and skeletal function. The crosstalk between sympathetic nerves and type H vessels in bone remains unclear. Here, we first identify close spatial connections between sympathetic nerves and type H vessels in bone, particularly in metaphysis. Sympathoexcitation, mimicked by isoproterenol (ISO) injection, reduces type H vessels and bone mass. Conversely, beta-2-adrenergic receptor (ADRB2) deficiency maintains type H vessels and bone mass in the physiological condition. In vitro experiments reveal indirect sympathetic modulation of angiogenesis via paracrine effects of mesenchymal stem cells (MSCs), which alter the transcription of multiple angiogenic genes in endothelial cells (ECs). Furthermore, Notch signaling in ECs underlies sympathoexcitation-regulated type H vessel formation, impacting osteogenesis and bone mass. Finally, propranolol (PRO) inhibits beta-adrenergic activity and protects type H vessels and bone mass against estrogen deficiency. These findings unravel the specialized neurovascular coupling in bone homeostasis and regeneration. [Display omitted] •Sympathetic nerves spatially and functionally correlate with type H vessels in bone•Sympathoexcitation regulates type H vessel formation and bone mass maintenance•Sympathetic cues regulate angiogenic signaling via an MSC-EC paracrine mode•Pharmacological ADRB inhibition protects type H vessels and bone mass in OVX Vascular anatomy; Orthopedics; Molecular neuroscience